2012
DOI: 10.1111/j.1532-5415.2012.03917.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Disease‐Specific Advance Care Planning Intervention on End‐of‐Life Care

Abstract: Background/Objectives Advance Care Planning (ACP) allows patients to state preferences for their end of life care but these preferences are frequently ignored. Following a Patient-Centered ACP interview (PC-ACP), patients’ preferences were compared to care received at end of life. Design A randomized controlled trial was conducted with patients with Congestive Heart Failure or End-stage Renal Disease and their surrogates who were randomized to receive either PC-ACP or usual care. Setting Two centers in Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
186
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(191 citation statements)
references
References 10 publications
5
186
0
Order By: Relevance
“…No study measured compliance with patient wishes for EOL care , arguably the most important outcome of ACP. The study by Kirchoff and colleagues found a non-significant trend towards influencing this outcome but was not appropriately powered 96 . Complex interventions like ACP also benefit from measurement models that link processes to outcomes so that mechanisms of effect can be understood and replicated or adapted in future 97 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…No study measured compliance with patient wishes for EOL care , arguably the most important outcome of ACP. The study by Kirchoff and colleagues found a non-significant trend towards influencing this outcome but was not appropriately powered 96 . Complex interventions like ACP also benefit from measurement models that link processes to outcomes so that mechanisms of effect can be understood and replicated or adapted in future 97 .…”
Section: Discussionmentioning
confidence: 96%
“…A "whole system" approach to ACP has been shown to be effective in improving outcomes for patients and their surviving relatives in other settings 10 , and may be similarly beneficial for renal patients. A study reported by Kirchoff and colleagues (2010, 2012) examined the effect of a comprehensive ACP intervention but could not be included because patients with CKD constituted only a minority (42%) of the sample, which was predominantly made up of patients with congestive heart failure 95,96 .…”
Section: Discussionmentioning
confidence: 99%
“…Supplying this kind of information about anticipated outcomes to patients embarking on a course of chronic dialysis may help to provide a realistic foundation for future treatment decisions that are aligned with their goals, values, and preferences. [25][26][27] Figure 1. Trends in the level of intensity of care received around the time of dialysis initiation.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Several studies have examined whether an ACP intervention promotes consistency between a patient's preferences and the treatments the patient actually receives near the end of life. [5][6][7][8] How such consistency was conceptualized and determined varied across the studies; in general a patient's early documented preferences were compared to medical record documentation of the end-of-life care the patient received (e.g., ICU admissions, CPR, mechanical ventilation, and location of death).…”
Section: Introductionmentioning
confidence: 99%